A Needs Analysis of Code-Mixed "Slice-of-Life" Fiction as Authentic Reading Materials for EFL Adolescents: Bridging the Gap Between Everyday Language and Classroom Literacy - Kintan Arsya Rizqia Ruslandi; Evi Karlina Ambarwati (Jurnal Educatio FKIP UNMA, 2026)
Reading comprehension is a critical skill for high school students, yet conventional textbooks often trigger learning boredom and anxiety due to their rigid structures. This qualitative descriptive study investigates how the integration of pop culture media and bilingual texts affects students' reading comprehension and engagement. Through purposive sampling, twelve 12th-grade students participated in asynchronous semi-structured interviews via WhatsApp Voice Notes. The findings reveal four key integration strategies: (1) utilizing visually appealing slice-of-life digital fiction to eliminate boredom; (2) leveraging code-mixing as a psychological comfort zone to reduce reading anxiety; (3) employing bilingual contextual clues for autonomous vocabulary acquisition; and (4) boosting intrinsic motivation for real-world English application. The study concludes that pop-culture-based bilingual materials bridge the gap between formal education and students' daily linguistic realities, fostering a more natural and engaging environment for language acquisition.